Antibacterial Activity Tests of Endophytic Bacteria Isolates From Tea Plant (Camellia sinensis) Againts Staphylococcus aureus and Staphylococcus epidermidis - Sari, Suli Arum; Pujiyanto, Sri; Suprihadi, Agung (Berkala Bioteknologi, 2022)
Staphylococcus is one of the most common types of bacteria in Asia that causes local infectious diseases of the skin, nose, urethra, vagina, digestive tract, pneumonia, endocarditis, septic arthritis, and septicemia. Staphylococcus aureus and Staphylococcus epidermidis are the most common types of Staphylococcus in Asia. Tea plants contain bioactive compounds and endophytic bacteria which are widely used as antimicrobial agents. Endophytic bacteria are bacteria that exist in plant tissues, not pathogenic, and have the ability as the host plant. The purpose of this study was to determine the antibacterial activity of endophytic bacterial isolates of tea plants (Camellia sinensis) against the growth of Staphylococcus aureus and Staphylococcus epidermidis bacteria. The antibacterial activity test of endophytic bacteria of tea plants includes a series of processes such as sample selection, surface sterilization of samples, isolation of endophytic bacteria in agar medium, purification, screening, suspension of endophytic bacteria in 0.9 % NaCl and standardized with 0.5 McFarland, making endophytic bacterial culture in nutrient borth, making endophytic bacterial supernatant and antibacterial activity test with paper disc diffusion method. The results obtained are the antibacterial activity of the endophytic bacterial supernatant isolates B23, B14, and A2 on the growth of Staphylococcus aureus and Staphylococcus epidermidis. The best antibacterial activity was found in endophytic bacterial B14 isolates with inhibition zones of 7.75 mm and 12.5 mm followed by B23 isolates with 7.5 mm and 8.25 mm inhibition zones and A2 isolates with large inhibition zones of 7.42 mm and 8.16 mm. Endophytic bacteria isolates of tea plant show better antibacterial activity against the growth of Staphylococcus aureus than Staphylococcus epidermidis.